2012
DOI: 10.1002/etc.1749
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effects of the herbicides chlortoluron and mesotrione on freshwater microalgae

Abstract: Extensive use of herbicides in agriculture is accompanied by the risk of environmental contamination of aquatic ecosystems. The present study shows the effects of the herbicides chlortoluron and mesotrione on three microalgae species: two chlorophyceae (Pediastrum tetras, Ankistrodesmus fusiformis) and one diatom (Amphora coffeaeformis). The authors calculated the IC50 for one chlorophyceae and the diatom. The order of toxicity (median inhibitory concentration [IC50]) for mesotrione was A. coffeaeformis (13.1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(12 citation statements)
references
References 51 publications
0
12
0
Order By: Relevance
“…Besides good properties of mesotrione for weed control, non-target organisms are exposed by additional toxic and harmful effects. Because of the low sorption of mesotrione in the soil, it has a tendency to leach to the groundwater during corn cultivation [ 2 ], where it causes negative consequences on the aquatic ecosystem [ 3 ]. In addition, toxic influence on Tetrahymena pyriformis nonspecific esterase activities Vibrio fischeri metabolism and may cause infestation of some sea life [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Besides good properties of mesotrione for weed control, non-target organisms are exposed by additional toxic and harmful effects. Because of the low sorption of mesotrione in the soil, it has a tendency to leach to the groundwater during corn cultivation [ 2 ], where it causes negative consequences on the aquatic ecosystem [ 3 ]. In addition, toxic influence on Tetrahymena pyriformis nonspecific esterase activities Vibrio fischeri metabolism and may cause infestation of some sea life [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Valiente Moro et al (2012) reported an IC 50 (half-maximum inhibitory concentration) of 50 µg.L -1 on the freshwater phytoplankton Ankistrodesmus fusiformis. Although this concentration is higher than those commonly found in the Pertuis Charentais, it is quite close to the maximum concentrations detected in some European rivers.…”
Section: Experimental Concentrations Versus Natural Environmentmentioning
confidence: 99%
“…Chlortoluron that belongs to substituted urea family is one of the most commonly used herbicides in wheat and barley crops. Chlortoluron inhibits photosynthesis and affects phytoplankton (Valiente Moro et al, 2012). In 2017, a maximum value of 0.18 μg.L -1 was detected at the mouth of a river (surface water) flowing into the Pertuis Charentais (Leonard, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…52,100 tons of organic pesticides, equating to more than 500 different active substances, were used in France in 2009 [50]. In 2000, the nation used 5033 tons of phenylurea herbicides, including chlortoluron, one of the most popular herbicides due to its long half-life in soil (30-40 days).…”
Section: Prevalencementioning
confidence: 99%